Application of the Crossword Puzzle Method in Overcoming the Difficulty of Reading Arabic Pegon on Santri at Madrasah Diniyah Takmiliyah Al-Fithroh Sedayulawas Brondong Lamongan - M. Fazlurrahman Hadi; Adela Yuana Ramadhani; Ika Puspitasari (Madrosatuna: Journal of Islamic Elementary School, 2022)
Arab Pegon is a scientific heritage of the scholars of the archipelago that must be preserved. Madrasah Diniyah Takmiliyah al-Fithroh Sedayulawas Brondong Lamongan is the only madrasa in Sedayulawas village that still preserves learning using Arabic Pegon. The habit of using Latin writing, with traditional learning methods, makes the students have difficulty reading Arabic Pegon. To overcome this problem, the researchers conducted learning using the crossword puzzle method on the Date material. The aims of this study were to (1) describe the Arabic Pegon Learning for Santri at the Madrasah Diniyah Takmiliyah Al-Fithroh Sedayulawas Brondong Lamongan, (2) to describe the application of the crossword puzzle method in overcoming the difficulty of reading Arabic Pegon at the Madrasah Diniyah Takmiliyah Al-Fithroh Sedayulawas Brondong Lamongan. This research method uses descriptive qualitative research with the type of case study research. Data collection techniques in this study were observation, interviews, and documentation. The data sources in this study consisted of two sources, namely primary data sources and secondary data sources. The results of this study indicate that the application of the crossword puzzle method in overcoming the difficulty of reading Arabic Pegon in grade III early Islamic students in the data subject has been carried out well. In terms of the initial reading ability, the students experienced an increase in distinguishing the shape of the Arabic letter Pegon and sounding the Arabic vowel Pegon fluently. The ability to read and understand students' reading comprehension has also increased which includes reading comprehension of words, content assessment, reading speed, improving students' abilities in writing Arabic Pegon, and the spirit of learning Arabic Pegon.